2012
DOI: 10.1111/ede.12002
|View full text |Cite
|
Sign up to set email alerts
|

Early cleavage in Phoronis muelleri (Phoronida) displays spiral features

Abstract: The view that early cleavage in Phoronida follows a radial pattern is widely accepted. However, data supporting this characterization are ambiguous. Studies have been repeatedly reporting variation between individual embryos, and the occurrence of embryos exhibiting oblique divisions or nonradial cell arrangements. Such embryos were often considered to represent variation within radial cleavage, or artificial appearances. Cleavage in Phoronis muelleri was previously characterized as "derived radial," but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Alternatively one might assume that Lophophorata is the sister group of the lophotrochozoan phyla that share spiral cleavage. However, the finding that cleavage is spiral in at least some phoronids [59,60] shows how variable cleavage patterns are and that the radial cleavage of lophophorates is probably secondarily derived from spiral cleavage.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively one might assume that Lophophorata is the sister group of the lophotrochozoan phyla that share spiral cleavage. However, the finding that cleavage is spiral in at least some phoronids [59,60] shows how variable cleavage patterns are and that the radial cleavage of lophophorates is probably secondarily derived from spiral cleavage.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is no obvious consensus for the relationships between them. Brachiopods and phoronids are very likely linked -phoronids may even be shell-less brachiopods -and molecular phylogenies and recent reports of spiral cleavage link these two phyla to the spirally cleaving annelids, molluscs and nemerteans [42]. The spiral cleavage and trochophora-like Mü ller's larva of some platyhelminths also suggests a link to these phyla.…”
Section: Major Areas Of Phylogenetic Controversymentioning
confidence: 96%
“…The recognition that the Lophotrochozoa are monophyletic -a clade that includes all the phyla with classic spiral cleavage -strongly supports the homology of this mode of early development. Recent reports of spiral cleavage in the lophophorate phoronids [42] and in entoprocts [43] make sense in the light of their inclusion in the Lophotrochozoa alongside the canonical spiral cleavers.…”
Section: Evolution Of Early Embryonic Cleavage Patternsmentioning
confidence: 99%
“…Although irregular early cleavage stages have been observed (Zimmer 1964 ;Malakhov and Temereva 2000 ), none of these patterns exhibit spiral-like divisions. At the four-cell stage, transient cell contacts between non-sister blastomeres do occur, creating a crossfurrow similar to what is described for Phoronis muelleri (Pennerstorfer and Scholtz 2012 ).…”
Section: Early Developmentmentioning
confidence: 61%
“…Cleavage variation also begins at different early cleavage stages among species; some cleave variably at the eight-cell stage (Brooks and Cowles 1905 ;Herrmann 1986 ) and others (more commonly) at the 16-cell stage (Temereva and Malakhov 2007 ). More recently, early cleavage was investigated in Phoronis muelleri using 4D microscopy techniques (Pennerstorfer and Scholtz 2012 ), which showed that oblique rather than perpendicular cell divisions occurred at third and subsequent cleavages of most of the embryos in the study. Interestingly, cell divisions at third cleavage and beyond also exhibited alternating dextral-sinistral twists, a feature typical of spiralian embryos (Hejnol 2010 ).…”
Section: Early Developmentmentioning
confidence: 99%